The effect of 800 μg and 1600 μg inhaled salbutamol on FEV1 in non-asthmatic football players. Issue 15 (10th November 2011) - Hu, J; Dickinson, J; Chester, N; Drust, B; Whyte, G; Loosemoore, M
Abstract : The World Anti-doping Agency stipulates that athletes who declare the use of salbutamol should not exceed 1600 μg over a 24 h period. Most studies investigating the effect of inhaled salbutamol on maximal flow volume values, such as FEV1, have investigated doses of up to 800 μg of salbutamol. The purpose of this study was to investigate the effect of inhaling 800 μg or 1600 μg on the FEV1 in non-asthmatic football players. Five male non-asthmatic football players (mean+SD; age 24+4 y; weight 71+4 kg; height 175+5 cm) volunteered. Participants attended the laboratory on six occasions to inhale either a placebo, 800 μg of salbutamol or 1600 μg salbutamol and complete a football-specific run. Maximal Flow Volume Loops were measured at baseline, 10 min following inhalation of salbutamol or placebo and 5 min following the football specific run. Repeated measures ANOVA were performed to investigate the changes in FEV1 10 min post salbutamol and post football specific treadmill run. Significance was assumed if p<0.05. There was a significant difference (p=0.02) between FEV1 following the inhalation of either 800 μg (4.4+0.5 l) or 1600 μg (4.4+0.4 l) salbutamol when compared to placebo (4.3+0.5 l) prior to the football-specific run. This significant difference was maintained following the completion of the football specific run following the inhalation of either 800 μg or 800 μg (4.5+0.5 l) or 1600 μg (4.5+0.5 l) salbutamol when compared placebo (4.3+0.5 l). The improvements in FEV1 following the inhalation of 800 μg or 1600 μg salbutamol prior to the football-specific treadmill run appears to suggest there is a potential for significant bronchodilation in the airways of non-asthmatic football players. The difference in FEV1 between placebo and salbutamol appears to be maintained following the completion of a football-specific treadmill run.